Aortic distensibility and stiffness index measured by magnetic resonance imaging in patients with Marfan's syndrome. Issue 3 (March 1995) - Adams, J. N.; Brooks, M.; Redpath, T. W.; Smith, F. W.; Dean, J.; Gray, J.; Walton, S.; Trent, R. J.
Abstract : OBJECTIVES–To use magnetic resonance imaging to measure the elastic properties of the aorta of adults with Marfan's syndrome and to compare these results with those obtained by echocardiography. PATIENTS AND METHODS–12 patients with Marfan's syndrome and 12 controls matched for age. Transverse luminal areas of the ascending and descending aorta were measured using electrocardiographic gated magnetic resonance imaging. Echocardiography was used to measure the diameter of the ascending aorta and aortic arch in patients with Marfan's syndrome. Blood pressure was measured during both scans. RESULTS–In diastole, transverse luminal areas of the ascending and descending aorta were significantly greater in patients with Marfan's syndrome when measured by magnetic resonance imaging and corrected for body surface area; P < 0.02 and P < 0.05 respectively. Patients with Marfan's syndrome had a higher stiffness index (112.77 v 5.78, P < 0.05) and a lower distensibility (0.0066 v 0.0105, P < 0.05) than controls. Results produced by MRI and echocardiography were not significantly different. CONCLUSIONS–Magnetic resonance imaging gives good quality reproducible images of the ascending and descending aorta. In patients with Marfan's syndrome, aortic distensibility and stiffness index measured by magnetic resonance imaging were abnormal (but did not always relate directly to the size of the aorta.